Oxford handbook of tropical medicine. - Davidson, Robert (Robert N.); Brent, Andrew (Physician); Seale, Anna; Blumberg, Lucille (Oxford : Oxford University Press, 2021)
The new edition of this handbook continues to provide an accessible and comprehensive, signs-and-symptoms based source of information on medical problems commonly seen in the tropics. A practical guide to diagnosis and management for medical practitioners and students, it provides vital information at the reader's fingertips.
This edition also issued in print: 2022.
Previous edition: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 19, 2021).
Keywords: Tropical medicine; Health and Wellbeing; Clinical & internal medicine